In Vitro Prevention of Salmonella Lipopolysaccharide-Induced Damages in Epithelial Barrier Function by Various Lactobacillus Strains - Yeung, Chun-Yan (Hindawi Publishing Corporation, 2013)
Background. Lactobacillus shows beneficial anti-inflammatory effects on Salmonella infection. The maintenance of the tight junction (TJ) integrity plays an importance role in avoiding bacterial invasion. Whether Lactobacillus could be used to regulate the TJ protein expression and distribution in inflamed intestinal epithelial cells was determined. Methods. Using the transwell coculture model, Salmonella lipopolysaccharide (LPS) was apically added to polarized Caco-2 cells cocultured with peripheral blood mononuclear cells in the basolateral compartment. LPS-stimulated Caco-2 cells were incubated with various Lactobacillus strains. TJ integrity was determined by measuring transepithelial electrical resistance across Caco-2 monolayer. Expression and localization of TJ proteins (zonula-occludens- (ZO-) 1) were determined by Western blot and immunofluorescence microscopy. Results. Various strains of Lactobacillus were responsible for the different modulations of cell layer integrity. LPS was specifically able to disrupt epithelial barrier and change the location of ZO-1. Our data demonstrate that Lactobacillus could attenuate the barrier disruption of intestinal epithelial cells caused by Salmonella LPS administration. We showed that Lactobacillus strains are associated with the maintenance of the tight junction integrity and appearance. Conclusion. In this study we provide insight that live probiotics could improve epithelial barrier properties and this may explain the potential mechanism behind their beneficial effect in vivo.